Arthroscopic Modified McLaughlin Procedure and Posterior Labral Repair in the Lateral Decubitus Position - Te-Feng A. Chou, M.D.; Eloy Tabeayo, M.D.; Konrad I. Gruson, M.D. (Arthroscopy Techniques, 2025)
Traumatic posterior shoulder dislocations are commonly associated with a posterior labral tear and an impaction fracture involving the anterior humeral head referred to as a reverse Hill-Sachs lesion (RHSL). This humeral defect can engage on the posterior glenoid rim during shoulder cross-body adduction combined with shoulder elevation and may require surgical intervention. Depending on the size of the RHSL relative to the articular arc of the humeral head, traditional open surgical options including transfer of the subscapularis tendon alone, subscapularis transfer with the attached lesser tuberosity into the humeral impaction injury, or reconstruction using allograft for more severe defects have been described. We present an all-arthroscopic technique performed in the lateral decubitus position involving concomitant repair of the posterior labral tear and transfer of the subscapularis tendon (reverse remplissage or arthroscopic modified McLaughlin procedure) into a moderately sized RHSL.